PENGARUH MACAM PUPUK DAN PESTISIDA ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI HITAM INFLUENCE OF KINDS OF ORGANIC PESTICIDE AND MANURE TO GROWTH AND RESULT OF BLACK PADDY CROP ( Oryza Sativa L) - Hadi, Pramono -; -, Sarwono - (Innofarm:Jurnal Inovasi Pertanian, 2013)
ABSTRACK Influence Research of kinds of this organic pesticide and manure aim to to know the growth and result of black paddy crop. Research have been executed [at] this Research have been executed at november 2012 until February month; moon 2012 in Countryside Gebang, Subdistrict Masaran, Regency Sragen, Central Java, with the type of land;ground grumosol of at place height 100 metre of is above sea level. This research use the factorial method with the elementary pattern of Random Device of Complete Group and consisted of by three treatment factor repeated by thrice. As for three the treatment factor shall be as follows : Fertilize the Cage ( P) consisted of by 3 kinds of treatment ( P1) : Fertilize the cow shed 30 ton / ha, ( P2) : Fertilize the quill Cage 30 ton / ha, ( P3) : Fertilize the sheep fold 30 ton / ha. Kinds of pesticide organic : (V1) : Pesticide with the leaf Bail the, ( V2) : Pesticide with the Clove leaf, ( V3) : Pesticide with the Tobacco Treatment of kinds of cage manure, having an effect on reality to high of crop, sum up the productive tillers, fresh weight of stove , sum up the shell of rice fill the per panicle contents, heavy of dry shell of rice mill the rice per hill and dry shell of rice weight mill the per-plot. Treatment of kinds of cage manure, difference is not real to weight of shell of rice 1000 item and Sum up the vacuous shell of rice of per panicle contents. Treatment of kinds of different organic pesticide very real at vacuous shell of rice Amount of per panicle contents of but difference is not real at high of crop, sum up the productive tillers, fresh weight of stover, sum up the shell of rice fill the per panicle, heavy of dry shell of rice mill the rice per hill, heavy of dry shell of rice mill per-plot. Interaction of among/between treatment of kinds of kinds of organic pesticide and manure of difference is not be high real crop, sum up the productive tillers, fresh weight of stover, heavy of shell of rice 1000 item, sum up the shell of rice fill the per panicle, Sum up the vacuous shell of rice of per panicle, heavy of dry shell of rice mill the per panicle and dry shell of rice weight mill per-plot.   Keywords: Pestiside And kinds Organic BlackPaddy *) Pramono Hadi  : Dosen Fakultas Pertanian UNIBA Surakarta **) Sarwono         : Dosen Fakluiltas Pertanian UNISRI Surakarta